Adorno's Aesthetics of Music - Paddison, Max (Cambridge Cambridge University Press, 1993)
The main aim of this book is to provide a conceptual context within which to situate Adorno's writings on music. It has quickly established itself as a classic text. Paddison surveys the early writings from the 1920s and examines Adorno's idiosyncratic reception of Marx and Freud. He then discusses Adorno's approach to analysis, and to the sociology of music, and his philosophy of history. The study closes with a critical assessment of Adorno's concept of musical material in the context of his best-known book Philosophy of New Music.
Keywords: Adorno, Theodor W. -- 1903-1969; 20th Century (1901-2000); Music philosophy and esthetics; Germany